Photocontrolled reversible-deactivation radical polymerization of butyl acrylate mediated by Salen-type CoII complexes - Oliveira, Larissa F. [UNESP]; Bignardi, Camila [UNESP]; Pesqueira, Naralyne M. [UNESP]; Riga-Rocha, Beatriz A. [UNESP]; Machado, Antonio E.H.; Carvalho-Jr, Valdemiro P. [UNESP]; Goi, Beatriz E. [UNESP] (Elsevier, 2021)
In this study, we synthesized the complex [Co(BuSalen)] using the novel tetradentate BuSalen ligand and analyzed its ability as a controlling agent for the photo-induced organometallic-mediated radical polymerization (photo-OMRP) of butyl acrylate (BA) using diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) as photo-initiator. BA polymerization with [Co(BuSalen)] reached significant control levels using the [BA]/[CoII]/TPO molar ratio of 600/1/1. The [Co(Salen)] and [Co(Bu2Salen)] complexes were also obtained following literature methods aiming a comparison in the mediating ability in photo-OMRP. [Co(BuSalen)] and [Co(Bu2Salen)] showed better controlling ability, as observed in the copolymerization study (Đ= 2.64, 1.50, and 1.26 for complexes [Co(Salen)], [Co(BuSalen)] and [Co(Bu2Salen)], respectively). Kinetics studies and computational investigations support a reversible termination (RT) mechanism and a tailorable CoII complex reactivity mainly altered by Schiff-base steric factors. Calculated thermodynamic parameters agree with the controlling degree delivered by these complexes, since the polymerization control increases with increasing the ΔG values for the formation of dormant species.
Keywords: Butyl acrylate; CoII complexes; Photo-OMRP; Tetradentate Schiff-base